KONSEP PENDIDIKAN DALAM ISALM TELAAH PEMIKIRAN AL GHAZALI DAN IBNU SINA - Farihah Chalimatus Sadiyah; Ahmad Mustafidin (As-Sulthan Journal of Education, 2025)
Education in Islam has a unique and comprehensive concept, which not only includes intellectual aspects but also spiritual and moral aspects. This article examines the thoughts of two great figures in the Islamic world, namely Al-Ghazali and Ibn Sina, regarding the concept of education. Al-Ghazali emphasized the importance of education as a means of purifying the soul and approaching Allah, while Ibn Sina highlighted the intellectual and pedagogical development aspects in education. This research was conducted using a qualitative method based on literature studies of the main works of both figures. The results of the study show that although both have different perspectives, their concept of education remains